Texts and computations, mechanisms and abstractions. Dualism and digital editions - Meschini, Federico (JLIS.it, 2019)
Critical thinking on digital editions, and in particular scholarly editions, has been so far mainly focused on redefining the theoretical aspects developed in an analogical dimension, such as textual orientations, following a technological approach. In order to better understand the nature of digital editions it is also necessary to take into account aspects related to the theoretical dimension of computer science, since a technological approach, although initially justifiable, has several limitations due to the rapid and continuous changes in technology. For this reason, it is needful to apply other principles in the analysis and consideration of digital editions if we are to better understand their role in both Digital Humanities and in the dialogue between Humanities and the Hard Sciences, represented by the intertwining of narration and computation.